Assessment of zinc concentrations in surface sediment from urban and industrial sites of Umeda River, Japan - Wardhani, Widyastuti Kusuma (International Water Association, 2022)
Heavy metal contamination in the urban river has become the most severe problem in the urban environment, especially the zinc (Zn) compound is harmful to the environment at current levels of exposure. This study aims to assess the impact of urbanization and industrialization on Zn pollution in surface sediment at the Umeda River. Triplicate surface sediment samples were collected at nine sample points. An atomic absorption spectrophotometer was used for analyzing the Zn and Fe concentrations. The surface sediments in the Umeda River contained 48–159 mg/kg of Zn. The results indicated that Zn concentrations were abundant in the ascending order of 600–1,000 μm, 300–600 μm, and smaller than 300 μm. The higher the grain size, the higher the particulate organic carbon which might contribute to the higher Zn and Fe concentrations. In addition, the sediment quality guidelines indicated that the Zn levels in the study area did not constitute a major threat to biota. Normalization with Fe showed that the Zn pollution in surface sediment had been influenced by anthropogenic activities such as industrialization and urbanization.